THE EFFECTIVENESS OF IMPLEMENTATION OF LAW 35 YEAR 2009 ABOUT NARCOTIC OFFENSES IN MAKASSAR. - Prasetio Edy Wibowo; Hambali Thalib; Ma’ruf Hafidz (Meraja journal, 2020)
[Full Paper] to pdf Copyright (c) 2020 Meraja journal